Controlling fingermark variability for research purposes: A review. Issue 4 (15th May 2019) - Steiner, Romain; Roux, Claude; Moret, Sebastien
Abstract: Fingermark detection is a very active field of research in forensic science, with many different strategies currently investigated to always improve detection rate. However, each new technique has first to be optimized, assessed and validated with many fingermarks from multiple donors across a wide variety of substrates before being included into laboratories operating procedures. This process often requires the collaboration of research groups and operational laboratories from different countries, and it takes several years for a new method to be applied routinely in casework. One particular challenge that makes the process from R&D to operations complicated is the significant intrinsic within‐ and between‐source variability of fingermarks. Many studies partially addressing fingermark variability have been reported but a comprehensive approach to the problem is yet to be found. This review describes the factors of fingermark variability and provides an extensive overview of various strategies implemented to control it. The use of artificial fingermarks or simulants, containing some of the most abundant compounds found in fingermark residue has been investigated by some research teams. However, most of these formulations are too simplistic and can only be used to assess a restrictive number of detection techniques, such as amino acid reagents. Practical applications of artificial fingermarks such as test strips and proficiency testing are reviewed. The advantage and challenges of using artificial fingermarks in the first stages of fingermark detection research are presented. This article is categorized under: Forensic Chemistry and Trace Evidence > Fingermarks and Other Marks Abstract : Chemical and physical parameters both have a significant impact on the quality of a deposited fingermark and its subsequent processing with any detection technique.